On the crossover effects of Brexit and COVID-19 - Niklas Rohde (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2024)
This study is the first to investigate the crossover effect of the UK's exit from the European Union, com-monly referred to as Brexit, and the COVID-19 pandemic. First, we confirm the results of studies explor-ing Brexit and respond to critiques of the literature. By applying the synthetic control group method, this paper reveals the impact of Brexit on GDP per capita (up until the most recent data) has been negative. In a second step, we show that, while COVID-19 had a negative impact on all developed economies, the confluence of the two events resulted in considerably more adverse outcomes in the United Kingdom.
Keywords: E65; F13; F15; F55; 330; Brexit; COVID-19; Great Britain; growth